Палеолітична стоянка Галич ІІ: проблеми стратиграфії та хронології - Богуцький, А.; Ланчонт, М.; Ситник, О.; Мадейська, Т.; Кусяк, Я.; Федорович, С.; Дмитрук, Р.; Яцишин, А.; Думас, І.; Голуб, Б. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
Paleolithic site Halych II is situated in southern environ of town of Halych (Ivano-Frankivs’k region) on the upper part of cape-like projection of V terrace of Dnister River. Seven years (from 2002), almost every season, international group of researchers carried out explorations of the site to obtain new geological and archaeological data. Geological structure of Halych II is very complicated and it makes archaeological interpretation of this site complex too. During the years geomorphological, geological, malacological and archaeological researches were carried out, radiocarbon and TL-dating of deposits were made. This article deals with hypothesis of explorers of Halych II about possible variants of initial deposition of Paleolithic cultural layers and causes of their displacement during Pleistocene period.